IDENTIFIKASI DAN PENETAPAN KADAR PENGAWET BENZOAT PADA SAUS TOMAT PRODUKSI LOKAL YANG BEREDAR DI PASARAN KOTA MANADO - Kaunang, Jurike; Fatimawali, Fatimawali; Fatimah, Feti (UNIVERSITAS SAM RATULANGI, 2012)
This paper reports the identification and determination of benzoate preservative level intomato sauce on the market in Manado. Extraction of the benzoate with diethylether anddetermination of the preservative (benzoic acid) was determined using UV-Visspectrophotometer. Qualitatively, it was found that the sauce samples contained benzoate.Quantitatively, it was found that four samples of tomato sauce used benzoate as apreservative. two of them used benzoic above the threshold set uot in Decree No. Permenkes.722/Menkes/Per/IX/88.Keywords: benzoate, ketchup, Manado, spectrophotometer UV- Vis.